GO Programming in easy steps - Mcgrath, Mike (In Easy Steps Limited, 2020)
GO Programming in easy steps has an easy-to-follow style that will appeal to anyone who wants to begin coding computer programs with Google's Go programming language. The code in the listed steps within the book is color-coded making it easier for beginners to grasp. You need have no previous knowledge of any computer programming language so it's ideal for the newcomer. GO Programming in easy steps instructs you how to write code to create your own computer programs. It contains separate chapters demonstrating how to store information in data structures, how to control program flow using control structures, and how to create re-usable blocks of code in program functions. There are complete step-by-step example programs that demonstrate each aspect of coding, together with screenshots that illustrate the actual output when each program is executed. GO Programming in easy steps begins by explaining how to easily create a programming environment on your own computer, so you can quickly begin to create your own working programs by copying the book's examples. After demonstrating the essential building blocks of computer programming it describes how to use data abstraction for object-oriented programming and demonstrates how to code goroutines and channels for concurrency in your programs. Table of Contents